Biomechanical analysis of the effects of footwear - Fukano, M. (Sports injuries and prevention, 2015)
In this chapter I utilize a biomechanical approach in order to better understand the effects of footwear. In the first half of the chapter I describe the changes in lower extremity kinematics that occur during walking and running. In the second half I provide a new approach for the examination of foot and ankle kinematics and focus on the effects of footwear.